2023
DOI: 10.1111/head.14641
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in cluster headache: A systematic review

Marie‐Louise K. Søborg,
Rigmor H. Jensen,
Mads Barloese
et al.

Abstract: ObjectiveTo systematically investigate previously examined biomarkers in blood, urine, cerebrospinal fluid, tear fluid, and saliva of patients with cluster headache.BackgroundCluster headache is a condition with extensive clinical challenges in terms of diagnosis and treatment. Identification of a biomarker with diagnostic implications or as a potential treatment target is highly warranted.MethodsWe conducted a systematic review including peer reviewed full text of studies that measured biochemical compounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…In concordance with our data, previous studies have shown that there is no systemic in ammation in CH patients [4,37].…”
Section: Discussionsupporting
confidence: 94%
“…In concordance with our data, previous studies have shown that there is no systemic in ammation in CH patients [4,37].…”
Section: Discussionsupporting
confidence: 94%